Custer lesson in leadership - Schultz, Duane (Great generals series, 2010)
Custer was one of those larger-than-life figures, whose flamboyant, daring, and dashing personality vigorously defied conventional standards and became symbols of invincibility. Here, military historian Duane Schultz explores the strategies and legacy of one of the most fascinating figures in American military history.